DNA damage contributes to age‐associated differences in SARS‐CoV‐2 infection. Issue 12 (18th October 2022) - Jin, Rui; Niu, Chang; Wu, Fengyun; Zhou, Sixin; Han, Tao; Zhang, Zhe; Li, Entao; Zhang, Xiaona; Xu, Shanrong; Wang, Jiadong; Tian, Shen; Chen, Wei; et al.
Abstract: Coronavirus disease 2019 (COVID‐19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), is known to disproportionately affect older individuals. How aging processes affect SARS‐CoV‐2 infection and disease progression remains largely unknown. Here, we found that DNA damage, one of the hallmarks of aging, promoted SARS‐CoV‐2 infection in vitro and in vivo. SARS‐CoV‐2 entry was facilitated by DNA damage caused by extrinsic genotoxic stress or telomere dysfunction and hampered by inhibition of the DNA damage response (DDR). Mechanistic analysis revealed that DDR increased expression of angiotensin‐converting enzyme 2 (ACE2), the primary receptor of SARS‐CoV‐2, by activation of transcription factor c‐Jun. Importantly, in vivo experiment using a mouse‐adapted viral strain also verified the significant roles of DNA damage in viral entry and severity of infection. Expression of ACE2 was elevated in the older human and mice tissues and positively correlated with γH2AX, a DNA damage biomarker, and phosphorylated c‐Jun (p‐c‐Jun). Finally, nicotinamide mononucleotide (NMN) and MDL‐800, which promote DNA repair, alleviated SARS‐CoV‐2 infection and disease severity in vitro and in vivo. Taken together, our data provide insights into the age‐associated differences in SARS‐CoV‐2 infection and a novel approach for antiviral intervention. Abstract : Our data suggest DNA damage contributes to age‐associated differences in SARS‐CoV‐2 infection and provide a novel target for anti‐viral intervention.